2018
DOI: 10.4172/2161-0444.1000490
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Efficacy of Partially Partitioned Fractions of Spondias mombin (Linn) Extracts (Root, Leaf and Stem Bark) against Clinical and Environmental Isolates

Abstract: The purpose this research work is to determine the antibacterial and antifungal assay of partitioned fractions of S. mombin (Linn) extracts against clinical and environmental isolates. The root, leaf and stem-bark of S. mombin were harvested and air-dried. The dried S. mombin was milled into powdered form using manual grinder. Powdered S. mombin (1 kg) each of the different S. mombin parts was extracted with 3 L of 70% (v/v) ethanol, ethyl acetate and distilled water for 72 h at room temperature. The SMRE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Previous studies have reported the presence of various bioactive compounds in S. mombin, including alkaloids, flavonoids, and phenols, which have been associated with antimicrobial activity [26]. Additionally, the effectiveness of S. mombin against antibiotic-resistant bacteria corroborates findings from other studies that have investigated the antimicrobial potential of plant extracts against multidrug-resistant pathogens [27].…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have reported the presence of various bioactive compounds in S. mombin, including alkaloids, flavonoids, and phenols, which have been associated with antimicrobial activity [26]. Additionally, the effectiveness of S. mombin against antibiotic-resistant bacteria corroborates findings from other studies that have investigated the antimicrobial potential of plant extracts against multidrug-resistant pathogens [27].…”
Section: Discussionsupporting
confidence: 77%
“…13 The Igbos used the decoction of the leaves to wash swollen faces. 11 The antimicrobial properties of parts of the Spondias mombin tree -leaves, stem bark and fruits -have been confirmed by numerous phytochemical studies. 14 .…”
Section: Introductionmentioning
confidence: 94%
“…The fruit decoction is used as a diuretic and febrifuge. 11 Tea made of Spondias mombin leaves and flowers relieves stomachache, biliousness and inflammation. Decoction of young leaves is used to treat diarrhoea and dysentery.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that S. mombin L. has bioactive compounds such as chlorogenic acid [ 36 ], ellagic acid, rutin, quercetin [ 37 ], flavonoids [ 38 ], carotenoids, and vitamin C [ 39 ]. These compounds are possibly responsible for many biological activities, which include antioxidant, anti-inflammatory [ 40 ], antibacterial [ 37 ], antifungal [ 15 ], and antiviral [ 35 ] activities, among others.…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Over the years, several pharmacological activities have been attributed to Spondias genus; these include antibacterial, antidepressant, antifungal, antioxidant, anti-inflammatory, antiviral, antipsychotic, anxiolytic, sedative, and molluscicidal actions, among others [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. These activities stem from its active compounds, such as carotenoids, caffeic acid, catechin, chlorogenic acid, ellagic acid, flavonoids, gallic acid, isoquercetin, rutin, and quercetin [ 6 , 9 , 14 , 15 ]. The main pharmacological applications and used plant parts of some species of genus Spondias will be further described in this review.…”
Section: Introductionmentioning
confidence: 99%